AutoCAD for dummies. - Grabowski, Ralph (For Dummies, 2022)
You're one step away from creating crystal-clear computer-aided drafts in AutoCAD Ever started an AutoCAD project, only to give up when you couldn't quite get the hang of it? Or do you have a project coming up that would really benefit from a few meticulously created drawings? Then you need the latest edition of AutoCAD For Dummies, the world's bestselling retail book about the wildly popular program. With coverage of all the important updates to AutoCAD released since 2019, this book walks you through the very basics of pixels, vectors, lines, text, and more, before moving on to more advanced step-by-step tutorials on three-dimensional drawings and models. Already know the fundamentals? Then skip right to the part you need! From blocks to parametrics, it's all right here at your fingertips. You'll also find: In-depth explanations of how to create and store your drawings on the web Stepwise instructions on creating your very first AutoCAD drawing, from product installation and project creation to the final touches An exploration of system variables you can tweak to get the best performance from AutoCAD Perfect for the AutoCAD newbie just trying to find their way around the interface for the first time, AutoCAD For Dummies is also a must-read reference for the experienced user looking to get acquainted with the program's latest features and essential drawing tips. Grab a copy today!.